2013
DOI: 10.1096/fj.12-226373
|View full text |Cite
|
Sign up to set email alerts
|

HSulf sulfatases catalyze processive and oriented 6‐O‐desulfation of heparan sulfate that differentially regulates fibroblast growth factor activity

Abstract: Sulfs are extracellular sulfatases that have emerged recently as critical regulators of heparan sulfate (HS) activities through their ability to catalyze specific 6-O-desulfation of the polysaccharide. Consequently, Sulfs have been involved in many physiological and pathological processes, and notably for Sulf-2, in the development of cancers with poor prognosis. Despite growing interest, little is known about the structure and activity of these enzymes and the way they induce dynamic remodeling of HS 6-O-sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 39 publications
3
65
0
Order By: Relevance
“…Together with the sulfatase reported here, however, only three GAG endosulfatases have yet been identified from animals (40) and bacteria (24). The roles of HS 6-O-endosulfatase in animals have been widely and actively studied in biological processes from embryo development to tumorigenesis (41)(42)(43). However, this enzyme has rarely been used as a tool for structurefunction studies of HS in vitro, which might be due to its low activity and instability.…”
Section: Discussionmentioning
confidence: 87%
“…Together with the sulfatase reported here, however, only three GAG endosulfatases have yet been identified from animals (40) and bacteria (24). The roles of HS 6-O-endosulfatase in animals have been widely and actively studied in biological processes from embryo development to tumorigenesis (41)(42)(43). However, this enzyme has rarely been used as a tool for structurefunction studies of HS in vitro, which might be due to its low activity and instability.…”
Section: Discussionmentioning
confidence: 87%
“…Seffouh and colleagues (43) have demonstrated that SULF1 and SULF2 share the same desulfation process, but with a different rate, whereas SULF1 showed a much stronger potency for in vitro desulfation of HS substrates. Moreover, data from the literature indicate that the substrate specificity of the SULFs remains unclear, because some methods are not sensitive enough to detect less abundant disaccharide units (26,43). However, in vivo and in vitro data indicate that these enzymes essentially exert their activity on UA2S-GlcNS6S units, which are found within HS S-domains, and to a much lesser extent on (UA-GlcNS6S) disulfated disaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to point out, however, that discrepancies were previously observed between in vitro and in vivo studies involving SULFs (26,43). In vitro, the enzyme activity of the SULFs has been studied after near-exhaustive digestion of the polysaccharide.…”
Section: -G Lc N S U a -G Lc N A C ( 6 S ) U A -G Lc N S ( 6 S ) U A mentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the level of 6-O sulfation modulates the activities of various signaling molecules, such as FGF, Wnt and Hh (Ai et al, 2003;Danesin et al, 2006;Dhoot et al, 2001;Ma et al, 2011;Seffouh et al, 2013;Uchimura et al, 2006). To determine whether 6-O sulfation is key in the regulation of stem cell activity during midgut regeneration, we first determined expression patterns of Hs6st in the midgut using a Hs6st::EGFP protein-trap allele (Nagarkar-Jaiswal et al, 2015).…”
Section: Heparan Sulfate Regulates Damage-induced Activation Of Isc Dmentioning
confidence: 99%